Efeitos regionais de investimentos em infra-estrutura de transporte rodoviário - Weslem Rodrigues Faria (2009)
The literature argues that infrastructure investments in Brazil can have strong impacts on some poor states, and contribute to decrease regional inequality. This paper combines two methodologies for the projection of impacts of transportation infrastructure policies (e.g. roads construction and renovation). The first one is an inter-regional computable general equilibrium model (CGE). The second one is a transportation network model. In order to exemplify the potentialities of using such methodologies, two road investment projects were selected from publicly available information: BR-101 project, connecting Feira de Santana and Natal, and the BR-163 project, between Guarantã do Norte and Santarém. The changes of transport costs, calculated by the transport model, provided the key input to the CGE model. The methodology used allowed the projection of the impact of investment on the economies of the states directly affected by the projects and also the impacts on other states. Another measure was used for an alternative to evaluate the projects efficiency, the marginal productivity of investment.